Transcriptional regulation by hypoxia inducible factors - Dengler, Veronica L.; Galbraith, Matthew D.; Espinosa, Joaquín M. (Critical reviews in biochemistry and molecular biology, 2014)
Abstract The cellular response to oxygen deprivation is governed largely by a family of transcription factors known as Hypoxia Inducible Factors (HIFs). This review focuses on the molecular mechanisms by which HIFs regulate the transcriptional apparatus to enable the cellular and organismal response to hypoxia. We discuss here how the various HIF polypeptides, their posttranslational modifications, binding partners and transcriptional cofactors affect RNA polymerase II activity to drive context-dependent transcriptional programs during hypoxia.